RNF43 Is an Early and Specific Mutated Gene in the Serrated Pathway, With Increased Frequency in Traditional Serrated Adenoma and Its Associated Malignancy. (October 2016) - Tsai, Jia-Huei; Liau, Jau-Yu; Yuan, Chang-Tsu; Lin, Yu-Lin; Tseng, Li-Hui; Cheng, Mei-Ling; Jeng, Yung-Ming
Abstract : RNF43 is an E3 ligase that suppresses the Wnt/β-catenin signaling pathway and is frequently mutated in microsatellite-unstable colorectal carcinoma. To investigate the pathogenetic role of RNF43 in the serrated pathway, we conducted mutation analysis of RNF43 in several types of colorectal neoplasms. RNF43 mutation was found in 2 of 20 (10%) sessile serrated adenomas, 10 of 36 (28%) traditional serrated adenomas, 7 of 37 (19%) traditional serrated adenomas with cytologic dysplasia, and 9 of 31 (29%) BRAF -mutated/microsatellite-stable colorectal carcinomas; however, no mutation was found in 30 tubulovillous/villous adenomas. All mutations were located upstream of the ring finger domain of RNF43 without clustering, which is distinct from the pattern described for microsatellite-unstable colorectal carcinoma. RNF43 mutation was closely associated with BRAF mutation but inversely associated with KRAS mutation in traditional serrated adenoma with or without cytologic dysplasia ( P =0.018 and 0.045, respectively). The finding of RNF43 mutation in sessile serrated adenoma and traditional serrated adenoma, but not in tubulovillous/villous adenoma, indicated that RNF43 mutation is an early and specific molecular aberration in the serrated pathway. The frequency of RNF43 mutation was significantly higher in traditional serrated adenoma with or without cytologic dysplasia and BRAF -mutated/microsatellite-stable colorectal carcinoma than sessile serrated adenoma. The unique molecular spectrum of these tumors suggests a stepwise neoplastic progression from sessile serrated adenoma to traditional serrated adenoma and BRAF -mutated/microsatellite-stable colorectal carcinoma, which should be recognized as the traditional serrated pathway to distinguish from the sessile serrated pathway. Abstract : Supplemental Digital Content is available in the text.